2005
DOI: 10.1007/s00482-004-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronische Radikulopathie

Abstract: Treatment of chronic low back pain exhibiting radicular symptoms poses a clinical problem that has not yet been solved. The technique of percutaneous minimally invasive neurolysis described by Racz is being performed increasingly to treat chronic radiculopathy. A total of 61 patients with corresponding symptomatology after screening for inclusion and exclusion criteria in the region of the lumbar spinal nerve were treated with the Racz catheter technique. Distinct clinical improvement was observed at the 3- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Both treatments were associated with good short-term relief with no differences noted between protocols, though only 13% reported significant benefit at 12-month follow-up. Prospective studies that included patients with spinal stenosis [45], post-lumbar surgery pain [46], and those with radiculopathy of any etiology [47] have also reported good, long-term benefit.…”
Section: Evidence For Effectivenessmentioning
confidence: 99%
“…Both treatments were associated with good short-term relief with no differences noted between protocols, though only 13% reported significant benefit at 12-month follow-up. Prospective studies that included patients with spinal stenosis [45], post-lumbar surgery pain [46], and those with radiculopathy of any etiology [47] have also reported good, long-term benefit.…”
Section: Evidence For Effectivenessmentioning
confidence: 99%
“…Many studies have reported similar findings which showed pain and disability scores are reduced by addition of hyper tonic saline [7][8][9][10][11] . The addition of hyper tonic saline during per cutaneous epidural adhesion lysis is consideration to add to the adhesion lysis of possible adhesions and fibrous tissues in the epidural and perineural space.…”
Section: Resultsmentioning
confidence: 61%